On the nature and significance of two mega Chalk dissolution pipe infills, Goring Gap, Chiltern Hills, south Oxfordshire, UK. Issue 3 (July 2016) - Worsley, Peter
Abstract: Two partially exposed infilled pipes hosted by chalk were revealed in excavations into a hillside some 50 m above the modern River Thames. The pipes are interpreted as collapse features induced by voids originating at depth rather than classical stream fed sinkholes. Two kinds of infill could be distinguished, sands tentatively assigned to the early Eocene Reading Formation (Lambeth Group) and gravels associated with the mid-Pleistocene Beaconsfield Terrace. The age of development can be constrained by the Thames terrace chronology and this implies major landscape changes due to fluvial erosion since initiation of the pipes some 2 Ma and a reactivation event about 1 Ma.